A comparison of work environment, job insecurity, and health between marginal part‐time workers and full‐time workers in Denmark using pooled register data. Issue 1 (23rd July 2021) - Nielsen, Helena Breth; Gregersen, Laura Stonor; Bach, Emma Steffensen; Dyreborg, Johnny; Ilsøe, Anna; Larsen, Trine Pernille; Pape, Kathrine; Pedersen, Jacob; Garde, Anne Helene
Abstract: Objectives: This study aimed to evaluate characteristics of the work environment, job insecurity, and health of marginal part‐time workers (8.0‐14.9 hours/week) compared with full‐time workers (32.0‐40.0 hours/week). Methods: The study population included employees in the survey Work Environment and Health in Denmark (WEHD) in 2012, 2014, or 2016 (n = 34 960). Survey information from WEHD on work environment and health was linked with register‐based information of exposure based on working hours 3 months prior to the survey, obtained from the register Labour Market Account. Associations between marginal part‐time work and work environment and health were assessed using logistic regression models. Results: Marginal part‐time workers reported less quantitative job demands, lower levels of influence at work, poorer support from colleagues and leaders, less job satisfaction and poorer safety, as well as more job insecurity. Results on negative social relations in the workplace and physical workload were more ambiguous. Marginal part‐time workers were more likely to report poorer self‐rated health, treatment‐requiring illness, and depressive symptoms compared with full‐time workers. Adjusting for characteristics of the work environment showed an indication of altered odds ratios for self‐rated health and depressive symptoms, whereas job insecurity did not. Conclusions: This study finds that marginal part‐time workers experience a poorer psychosocial work environment and safety, higher job insecurity, and poorer health than full‐time workers. Work environment characteristics may confound or mediate the association between marginal part‐time work and health. However, prospective studies are needed to determine the causal direction of the revealed associations.